IMPLEMENTATION OF A TELEGRAM BOT FOR REAL-TIME FLIGHT INFORMATION SERVICES AT SOEKARNO-HATTA INTERNATIONAL AIRPORT - Faiz Albanna; Dhiani Dyahjatmayanti; Ristiani Ristiani (JOISIE (Journal Of Information Systems And Informatics Engineering), 2025)
The increasing reliance on smartphones and instant messaging platforms has transformed how information is accessed, especially in public service environments such as airports. This study presents the development and evaluation of a Telegram bot designed to deliver real-time flight information at Soekarno-Hatta International Airport, supporting the Silent Airport initiative. Using the Waterfall development model, the bot was built through structured phases including data analysis, interface design, implementation, testing, and maintenance. The system integrates the AirLabs API and offers users personalized access to arrival, departure, and flight search features. A user experience survey involving 60 participants assessed four indicators using a 5-point Likert scale. The results showed high average scores: usefulness (4.38), ease of use (4.30), user satisfaction (4.30), and user acceptance (4.23). These scores indicate strong user approval, as they approach the maximum value of 5 on the Likert scale. Comparative analysis with traditional Flight Information Display Systems (FIDS) highlights the bot’s strengths in accessibility, personalization, and mobile integration. Despite minor issues with real-time data accuracy, the Telegram bot effectively complements existing airport infrastructure and aligns with evolving digital user behavior. This research supports the potential of instant messaging platforms to enhance public information services within smart airport ecosystems